ASSESSMENT FOR LEARNING (AFL)-BASED STUDENT WORKSHEETS: IMPROVING CRITICAL THINKING SKILLS IN BASIC CHEMISTRY LEARNING - Muchlis, Muchlis; Nasrudin, Harun; Agustini, Rudiana; Rusmini, Rusmini (Universitas Labuhanbatu, 2025)
Purpose – This study aims to describe AfL-based student worksheets as a means of improving students' critical thinking skills in Basic Chemistry learning.Methodology – This pre-experimental study employs a one-group pre-test post-test design. The data obtained were analyzed using a mean difference test and an N-gain score. Students' critical thinking skills are considered to have improved if there is a significant difference between the pre-test and post-test scores, and at least 55% of students in a class achieve a medium and/or high criterion of N-gain score.Findings – The mean difference test revealed a significant difference in the pre-test and post-test scores of students' critical thinking skills. The N-gain score measurement showed that the percentage of N-gain score in the medium and high criteria was higher than 55%. This implies that implementing AfL-based student worksheets can enhance students' critical thinking skills in Basic Chemistry Learning.Contribution – The research results reinforced previous findings that AfL implementation can improve students' critical thinking skills, especially in chemistry learning. In addition, feedback on the implementation of AfL can help students identify their strengths and weaknesses in learning, which they can use to improve their learning.